A Global Compendium of Oral Health Tooth Eruption and Hard Dental Tissue Anomalies. - Folayan, Morenike Oluwatoyin (Cambridge Scholars Publisher, 2019)
The book provides a summary of 30 countries' epidemiological profiles on tooth eruption and hard dental tissue anomalies. It opens with a chapter that introduces readers to the entire gamut of anomalies associated with tooth eruption, and dental tissue development and its associated anomalies. This is followed by a chapter that discusses dental development and its association with life history, brain development, and sexual maturity, as well as population differences in tooth development. There is also a contribution that extensively addresses teething and associated myths and misconception, w.